THE EFFECT OF KUR, UTILIZATIONE-COMMERCE, EDUCATION, AGE, AND GENDER ON THE INCOME OF KAMASAN WAYANG PAINTING MSMEs - Ni Komang Ayu Agustiana Putri; Ni Made Tisnawati (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the Indonesian economy, including in Bali Province. MSMEs also play a role in economic growth, especially in the craft industry such as Kamasan Puppet Painting. Kamasan Wayang Painting is a traditional art that grows and develops in Kamasan Village. The objectives of this research are: 1). To determine the influence of KUR, use of e-commerce, education, age and gender simultaneously on the income of Kamasan Wayang Painting MSMEs. 2). To determine the partial influence of KUR, use of e-commerce, education, age and gender on the income of Kamasan Wayang Painting MSMEs. The sample for this research consisted of 75 respondents. The data collection methods used in this research were observation, structured interviews and in-depth interviews. The data analysis technique used is multiple regression analysis. The research results show that simultaneously KUR, use of e-commerce, education, age and gender have a significant effect on the income of Kamasan Wayang Painting MSMEs. Partially, education and the use of e-commerce have no significant effect, while KUR, education, age and gender have a significant effect on the income of Kamasan Wayang Painting MSMEs. KUR, use of e-commerce, education, and age have a positive effect while gender has a negative effect on the income of Kamasan Wayang Painting MSMEs.